NIR‐I/III afterglow induced by energy transfers between Er and Cr codoped in ZGGO nanoparticles for potential bioimaging. Issue 9 (18th May 2021) - Yang, Jian; Jiang, Rongyun; Meng, Yangqi; Zhao, Yangyang; Wang, Mingwei; Zhu, Hancheng; Yan, Duanting; Liu, Chunguang; Xu, Changshan; Liu, Yuxue
Abstract: Herein, Cr 3+ and Er 3+ codoped zinc gallogermanate (ZGGO) nanoparticles with average size of ~60 nm was synthesized via a hydrothermal path. It was found that near infrared (NIR)‐III (~1540 nm) afterglow was realized in ZGGO:Cr 3+, Er 3+ nanoparticles based on the successive energy transfer (ET) from Cr 3+ to Er 3+ after the stoppage of low‐dose (60 mSv) X‐ray irradiation. Meanwhile, the upconverted afterglow at 696 nm was produced via the ET from Er 3+ to Cr 3+ under different NIR light (808, 980, and 1532 nm) irradiations. Our results demonstrated that an X‐ray pre‐irradiation and a subsequent 980‐nm light re‐excitation might be a good strategy for realizing potential bioimaging. In particular, local‐tissue NIR‐I afterglow imaging using Cr 3+ and Er 3+ codoped ZGGO nanoparticles can be easily acquired by one‐step 980‐nm laser radiation. Furthermore, NIR‐I/III afterglow mechanisms of ZGGO:Cr 3+, Er 3+ nanoparticles after stopping X‐ray or different NIR lights (808, 980, and 1532 nm) irradiations were given.